Perbedaan Perilaku Moral dan Religiusitas Siswa Berlatar Belakang Umum dan Siswa Sekolah Berlatar Agama - Firmansyah, Fitri Awan Arif; , Dr. Eny Purwandari, M.Si (2017)
The institution is a system that has an influence in shaping behavior and religiosity of students but not all educational institutions managed to change individual behavior for the better in the last few years a lot of cases amoral involving a student like brawl, ditching, in addition to educational institutions backgrounds other religion did not fully succeed in making the religiosity of students to be good a lot of students of religious schools do not pray berjama, ah school, truant, steal and violate the values of other religions. The purpose of this study is, to determine differences in moral behavior and religiosity of public school students and high school students religious background, hypothesis of this study was no difference in moral behavior and religiosity of public school students and students who attend school religious background. Subjects in this study were 160 students. The study used cluster random sampling study sampling technique Smaller or group. Data collection tools in this study using a scale of moral behavior and religiosity scale. Data analysis techniques in the development of this research using independent sample T-test analysis test.Hasil obtained in this study are :: There are significant differences of moral behavior and religiosity of public school students and religious schools. Perlaku higher moral public schools of religious schools and public schools Religiosity is higher than the religious schools. Keywords: Moral behavior, Religiosity, public schools, religious schools